The Use of GFRP Tubes as Load-Bearing Jackets in Concrete-Composite Columns - Abramski, Marcin; Chmielnicki, Błażej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the fields of applications of polymer composites in building structures. The use of composite glass fibre tubes is discussed in more detail. The laboratory methods used to test the mechanical properties of these pipes are presented. An original research program is presented, including six concrete-filled glass fibre tubes. The cylinders and columns made in this way were tested for their axial load capacity. Conclusions were formulated regarding the relationship between the load-bearing capacity of the test elements and their length, as well as the angle of glass fibres arrangement in the tube composite.
Keywords: composite structures; fibre-reinforced polymer; concrete filled tube; column; experiment; standardisation; konstrukcje kompozytowe; polimer wzmocniony włóknami; kolumna; eksperyment; standaryzacja